2019
DOI: 10.21203/rs.2.12328/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ANTIFUNGAL SUSCEPTIBILITY OF BIOFILM PRODUCING Candida albicans ISOLATED FROM ORAL CAVITY OF DIABETIC AND NON-DIABETIC POPULATION OF DHARAN, NEPAL

Abstract: Background: Candida are almost universal on normal adult skin and C. albicans is part of the normal flora of the mucous membranes of the respiratory, gastrointestinal, and female genital tracts. It is acknowledged that diabetic patients are more susceptible to infections caused by Candida albicans due to increased blood glucose and inability of immune system in eradicating the fungus. Studies suggest that Gutkha consumers are also at high risk of oral Candida carriage . Materials and methodology The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The link between diabetes and dry mouth has also been stated in additional studies. In one study of patients with diabetes, the outcomes contradict with our study, in which 5.4% of subjects testified dry mouth [15][16] . BMS is a chronic pain syndrome that has been testified with systemic ailments like diabetes and postmenopausal females 17 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The link between diabetes and dry mouth has also been stated in additional studies. In one study of patients with diabetes, the outcomes contradict with our study, in which 5.4% of subjects testified dry mouth [15][16] . BMS is a chronic pain syndrome that has been testified with systemic ailments like diabetes and postmenopausal females 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…Statistics from the diabetics and nondiabetic group exhibited that both groups had insufficient information of overall oral well-being [12][13] . Research on the awareness and knowledge of oral hygiene in patients with diabetes mellitus has shown that diabetic patients have deficiencies in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation